(untitled) (Journal of Medical & Health Sciences Review, 2025)
A progressive neurodegenerative condition connected with cognitive decline, Alzheimer’s disease (AD) is also known as Alzheimer’s disease. Although omega3 fatty acids have been proposed to have neuroprotective effects, their influence on early-stage AD remains underinvestigated. The impact of daily omega-3 supplementation on cognitive performance in adults with early-stage AD is assessed in this research. 45 individuals between the ages of 55 and 75, drawn from memory clinics and neurology departments using stratified random sampling, participated in a randomized controlled experiment. For six months, participants were randomly allocated to either a placebo group (n=22) or an omega3 supplementation group (n=23). At baseline and after intervention, cognitive performance was evaluated using the Montreal Cognitive Assessment (MoCA) and the Alzheimer’s Disease Assessment Scale-Cognitive Subscale (ADASCog). Mood and daily activities Were assessed with the Geriatric Depression Scale (GDS) and Activities of Daily Living (ADL) scale. Mean MoCA score following treatment was 24.1 ± 2.2 in the omega3 group compared to 23.0 ± 2.4 in the placebo group (p=0.04). The ADASCog scores fell by 2.0 ± 0.7 points p=0.03 for the omega3 group versus 0.9 ± 0.8 points in the placebo group. Enhancements in GDS and ADL scores were seen in the supplementation group, However, differences were not statistically significant (p>0.05). Omega3 supplementation for six months showed a slight but statistically significant improvement in cognitive function in patients with early-stage Alzheimer’s disease. These results show that omega-3 fatty acids might be a safe and supporting supplementary treatment to preserve cognitive function in early AD, therefore call for additional large-scale research.